Analysis of ductal carcinoma in situ by self-reported race reveals molecular differences related to outcome - Siri H. Strand; Kathleen E. Houlahan; Vernal Branch; Lorraine M. King; Thomas Lynch; Belén Rivero-Guitiérrez; Bryan Harmon; Fergus Couch; Kristalyn Gallagher; Mark Kilgore; Shi Wei; Angela DeMichele; et al. (Breast Cancer Research)
Abstract Background Ductal carcinoma in situ (DCIS) is a non-obligate precursor to invasive breast cancer (IBC). Studies have indicated differences in DCIS outcome based on race or ethnicity, but molecular differences have not been investigated. Methods We examined the molecular profile of DCIS by self-reported race (SRR) and outcome groups in Black (n = 99) and White (n = 191) women in a large DCIS case-control cohort study with longitudinal follow up. Results Gene expression and pathway analyses suggested that different genes and pathways are involved in diagnosis and ipsilateral breast outcome (DCIS or IBC) after DCIS treatment in White versus Black women. We identified differences in ER and HER2 expression, tumor microenvironment composition, and copy number variations by SRR and outcome groups. Conclusions Our results suggest that different molecular mechanisms drive initiation and subsequent ipsilateral breast events in Black versus White women.